2014
DOI: 10.1186/1471-2458-14-711
|View full text |Cite
|
Sign up to set email alerts
|

Drinking water source and human Toxoplasma gondii infection in the United States: a cross-sectional analysis of NHANES data

Abstract: BackgroundToxoplasma gondii imparts a considerable burden to public health. Human toxoplasmosis can be life-threatening in immunocompromised individuals, has been associated with psychiatric disorders, and can cause severe congenital pathologies, spontaneous abortion, or stillbirth. Environmental modes of transmission contributing to the incidence of human toxoplasmosis are poorly understood. We sought to examine National Health and Nutrition Examination Survey (NHANES) data for risk factors associated with T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 34 publications
(52 reference statements)
3
22
0
Order By: Relevance
“…In this study, we found that keeping cats at home was highly associated with T. gondii seropositivity (aOR 5·060, 95% CI 2·814-9·100, P < 0·001). Some previous reports have indicated that humans can become infected with T. gondii through ingesting tissue cysts in undercooked or raw meat from an infected intermediate host, or by ingestion of oocytes via unwashed vegetables and fruit or drinking water polluted by the faeces of an infected cat [4,[20][21][22]. Similarly, our study found that consumption of raw/undercooked meat was highly associated with T. gondii seropositivity (aOR 2·438, 95% CI 1·167-5·096, P = 0·018).…”
Section: Discussionsupporting
confidence: 66%
“…In this study, we found that keeping cats at home was highly associated with T. gondii seropositivity (aOR 5·060, 95% CI 2·814-9·100, P < 0·001). Some previous reports have indicated that humans can become infected with T. gondii through ingesting tissue cysts in undercooked or raw meat from an infected intermediate host, or by ingestion of oocytes via unwashed vegetables and fruit or drinking water polluted by the faeces of an infected cat [4,[20][21][22]. Similarly, our study found that consumption of raw/undercooked meat was highly associated with T. gondii seropositivity (aOR 2·438, 95% CI 1·167-5·096, P = 0·018).…”
Section: Discussionsupporting
confidence: 66%
“…Humans become infected postnatally, mainly by ingesting tissue cysts from undercooked meat or from food or drink contaminated with oocysts shed in cat feces [22, 34]. Ingestion of poorly cooked meat from sheep, and possibly consumption of non-pasteurized contaminated milk from sheep are considered important sources of transmission of T. gondii to humans [4, 7, 18, 21, 27].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of toxoplasmosis is most commonly made by detecting the immunoglobulin (IgG and IgG avidity) antibodies in the serum samples of patients using variety methods (ELISA, IFA, IgM-ISAGA, etc). [21][22][23][24][25] Sometimes, congenital toxoplasmosis received from undercooked meat. In spite of the fact that antibody to Toxoplasma is widely prevalent in human throughout the world, clinical toxoplasmosis is less common.…”
Section: Discussionmentioning
confidence: 99%